Predicting burnout and engagement in public secondary school teachers based on physical educational resources, positive organisational practices, psychological capital, work overload, and learner-to-teacher bullying - Pretorius, Annika (Stellenbosch : Stellenbosch University, 2023)
Thesis (MCom)--Stellenbosch University, 2023.